Studi pengaruh debit dan jumlah tingkat runner terhadap efisiensi turbin vorteks PLTPH - Haryadi, Haryadi; Mahmudi, Ali; Sugianto, Sugianto; Setiawan, Dibyo (JURNAL CRANKSHAFT, 2023)
Data from the Central Statistics Agency for West Java Province in the 2023 figures show that the installed electric power in 2022 is 30,196.9 MVA. Based on data from the Indonesia Energy Transition Outlook 2023, West Java Province is in the lowest classification with a percentage of 7-23%. An increase in the number of pico-hydro power plants with a low-head operating system can increase the distribution of electricity supply. Budget allocations for research are available at Polban for internal lecturers, through this scheme, the research team plans to increase the power and efficiency of vortex turbines, the 2023 research output target, an efficiency of 30% from the previous research achievement in the 2022 study of 23.8%. Current studies are carried out with variations in discharge and the number of runner stages to increase the efficiency of vortex turbines. The experimental operation is based on SNI 8277:2016, variations in discharge from 7 to 10 l/s, and the application of one and two stage 630 turbine runners. In addition to variations in discharge, loading gradually until the runner rotation stops. The results of the experimental recording of the application of the one-level 630 runner, obtained the highest efficiency occurring at a discharge of 9 l/s with an efficiency of 37%, while the experimental application of the two-level runner 630 highest efficiency occurred at the application of a discharge of 8 l/s with an efficiency of 34%. The more the discharge is added the response efficiency does not always increase.